2000
DOI: 10.1590/s0100-879x2000000300001
|View full text |Cite
|
Sign up to set email alerts
|

How are antibodies involved in the protective mechanism of susceptible mice infected with T. cruzi?

Abstract: Host resistance to Trypanosoma cruzi is dependent on both natural and acquired immune responses. During the acute phase of the infection the presence of IFN-g, TNF-a, IL-12 and GM-CSF has been closely associated with resistance, whereas TGF-ß and IL-10 have been associated with susceptibility. Several investigators have demonstrated that antibodies are responsible for the survival of susceptible animals in the initial phase of infection and for the maintenance of low levels of parasitemia in the chronic phase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…As shown in Fig. 5, in all mice immunized with the antigen-encoding plasmid (individually), a parasite-specific antibody response was elicited, with the maximal antibody level elicited in TcG2-and TcG4-immunized We monitored the agglutination-trypanolytic activity of the antigen-specific antibodies, since this property correlates with protection from T. cruzi infection (38,44). Considering that the epimastigote stage is susceptible to complement in an antibody-independent manner (12), we measured the agglutination of the epimastigotes after incubation with the antigenspecific polyclonal serum.…”
Section: Bioinformatic Analysis Of the Est And Gss Databasesmentioning
confidence: 99%
“…As shown in Fig. 5, in all mice immunized with the antigen-encoding plasmid (individually), a parasite-specific antibody response was elicited, with the maximal antibody level elicited in TcG2-and TcG4-immunized We monitored the agglutination-trypanolytic activity of the antigen-specific antibodies, since this property correlates with protection from T. cruzi infection (38,44). Considering that the epimastigote stage is susceptible to complement in an antibody-independent manner (12), we measured the agglutination of the epimastigotes after incubation with the antigenspecific polyclonal serum.…”
Section: Bioinformatic Analysis Of the Est And Gss Databasesmentioning
confidence: 99%
“…The maternal induction of such neonatal cell activation raises the question of its contribution in the control of congenital infection, since the neonates displaying such activation were uninfected (as verified by parasitological, PCR, and antibody detection). It is tempting to hypothesize that such newborns could be protected against an eventual vertical transmission of parasites, by a synergy between maternally transferred antibodies and acti- vated monocytes, previously shown to be effective in the in vitro and in vivo killing of parasites (32,33,44).…”
Section: Vol 68 2000mentioning
confidence: 99%
“…The protective role of the antibodies in the acute phase of the infection is dependent mostly on their ability to induce removal of trypomastigotes from the circulation, in addition to other concomitant cell-mediated events (Umekita & Mota 2000). It has been demonstrated that parasite-specific IgG, especially IgG2, recognizes a large number of parasite antigens and forms microaggregates that can fix complement, enhance opsonisation and mediate cytotoxicity mechanisms (Takehara & Mota 1991).…”
Section: Discussionmentioning
confidence: 99%